TIGA META-FUNCTIONAL PADA LAGU "THE POWER OF LOVE" KARYA CELINE DIONA: ANCANGAN LINGUISTIK FUNGSIONAL - Yusup Supyani (ELATICS JOURNAL, 2024)
The aim of this study is to analyze the song lyric of Celine Dion song “The Power of Love” with systemic functional linguistic approach. Theories applied in this research were three meta-functions, namely interpersonal function, ideational function and textual function from Halliday & Matthiessen (2014), Emilia (2014), and Supyani (2024). The method applied in this research was qualitative method to describe, analyze and interpret three-metafunctions occurred in the song lyrics of Celine Dion song “The Power of Love”. The data were collected by reading the lyrics of Celine Dion song, identifying three meta-functions, analyzing and interpreting three metafunctions including interpersonal function, ideational function and textual function. As a result of this analysis, the researchers found out that the majority of the song lyric used relational process and topical unmarked theme, which indicated that the song lyric of Celine Dion song was concise and meaningful. Keywords: Meta-functions, Ideational Function, Interpersonal Function, Textual Function